"I'm Just Who I Am": Self-Continuity and the Dialogical Self in a Study of Migrants. Issue 3 (3rd July 2019) - Bourke, Kenna; de Abreu, Guida; Rathbone, Clare J.
Abstract : Drawing on dialogical self theory, this study aimed to develop understanding of the processes of self-continuity in migrants with complex trajectories. Twelve participants of various nationalities and ages took part in qualitative interviews in the United Kingdom and the United States. An iterative, three-step analysis for multivoicedness suggested participants initially adopted stabilizing I-positions that acted as foundations for subsequent development and evolution of new selves. A clear and dynamic progression of positioning, repositioning, and innovation in the dialogical self emerged. Findings suggest that change and rupture may act as catalysts for positive development and innovation, resulting in a robust, enhanced sense of self-continuity.